Geographic influence on postoperative complications in children with complicated appendicitis: a single center study - Mohammad Seqsaqa; Ahmed Ezzat Rozeik; Mohammed Khalifa; Hazem Nour Abdellatif Ashri (SpringerOpen, 2021)
Abstract Background Acute appendicitis is one of the most common abdominal emergencies in children. Complicated appendicitis is much more common in pediatric age group than in adults due to probability of delay in diagnosis or misdiagnosis. Geographic status has an influence on the clinical course of such surgical cases. This prospective comparative study was conducted at the pediatric surgery department in our hospital in Egypt during the period from December 2018 to August 2019, aiming to find the relation between residence of patients and occurrence of post-operative complications among patients in Sharkia Governorate, Egypt. Patients were divided into two groups: rural and urban. Data recorded included demographic data, preoperative assessment, operative findings, postoperative course, postoperative complications, and follow-up. Results Sixty patients were included in the study, 32 of them were from rural areas, and 28 were from urban areas. There was no significant difference between them regarding demographics. Duration of symptoms was significantly longer with rural group (3.7 ± 1.4 vs. 3.07 ± 0.92 days). Length of hospital stay was significantly longer with the rural group (4.7 ± 1.7 vs. 4.7 ± 1.7 days). The rate of wound infection was significantly higher with the rural group (34.37% vs. 10.7%), while other postoperative complications were increased with rural group, but that was not statistically significant. The regularity of follow-up was higher with the urban group. Conclusions Children with complicated appendicitis from rural areas are at higher risk for occurrence of postoperative complications and poor outcome, with less regularity in follow-up. This is because of many obstacles they faced, including difficulties of transportation, insufficient medical services, and low socioeconomic and educational statuses.